BENTUK PENYAJIAN DAN FUNGSI MUSIK DALAM UPACARA THAU CHIT PADA AGAMA KHONGHUCU DI YAYASAN BUDI MULIA KECAMATAN LUBUK PAKAM KABUPATEN DELI SERDANG - KRISTIAN SINAGA (Universitas Negeri Medan, 2017)
Presentation Form And Function In Ceremony Thau Music Chit On Confucian Religion inYayasan Budi Mulia Lubuk Pakam District of Deli Serdang. Faculty of Language and Art. StateUniversity of Medan. This study aims to determine rites Chit Thau, the usefulness of theinstrument, the form of presentation and function of music in Chit Thau ceremony at the Confucianreligion in Yayasan Budi Mulia Lubuk Pakam District of Deli Serdang. This study is based on atheoretical foundation that explains the sense of form, sense of presentation, understanding thefunction, understanding music, understanding, Thau ceremony Chit, and understanding ofConfucianism. This research was conducted at Yayasan Budi Mulia Lubuk pakam District of DeliSerdang in June to August 2015. The method in this research use descriptive qualitative researchmethods. The population in this study is saikong (prayer leaders), community, and musicians atthe ceremony Thau Chit Confucian Religion in Yayasan Budi Mulia Lubuk Pakam District of DeliSerdang, while samples totaling 28 people. Data collected through observation, interviews,documentation, and strudi literature. These results indicate that the rites Thau Chit divided intoeight parts, namely Huat Piau is cleaning the altar and sending letters to the god of hell. WangPai is a tribute to the gods of heaven. Old Phou is the process invites the god of the earth. TiauHun is the process of summoning spirits. Mong Ek is the process of bathing spirit. Iok Pai Wang isa tribute to the god of medicine. Sio Ui house burning spirit. And Koei Kio is the return of thespirit of the gods .. Uses istrument music at the ceremony Thau Confucianism is Choei Chit Khinand Er Hu as a carrier melody, as rithem drums, bells and la Bua carrier tempo. Form ofpresentation of the music at the ceremony Thau Chit Confucianism is divided into three parts,namely musical homage to the gods, notification to the spirit, and the spirit returns to music.There are three functions of the music at the ceremony Thau Chit Confucianism, which is afunction of aesthetic pleasure and emotional expression, communication function and endorsementof religious rituals and functions contributes to the continuity and stability of culture.